Problems and properties of a new differential operator - Maslina Darus; Imran Faisal (Penerbit Universiti Kebangsaan Malaysia, 2011)
In this paper, we introduce and study a new differential operator defined in the open unit disc U={z:z€C^lzl<1}Using this operator, we then introduce a new subclass of analytic functions Gn(μ,λ,α,β,b). Moreover, we discuss coefficient estimates, growth and distortion theorems and inclusion properties for the functions belonging to the classGn (μ,λ,α,β,b) .